PENGARUH HARGA, GAYA HIDUP, DAN CORPORATE BRANDING TERHADAP KEPUTUSAN PEMBELIAN MOBIL LCGC DIKOTA MALANG (Studi Pada Customer Toyota Agya di Kota Malang) - MAULANA KEMAL ERTIASANIY ; Ananda Sabil Hussein, SE.,M.Com.,Ph.D.,CMA A
This research is motivated by the rapid development of the production and_x000D_ purchase of LCGC (Low Cost Green Car) in Malang. LCGC purchasing_x000D_ decisions that continue to increase in accordance with the needs of price, lifestyle_x000D_ and Corporate Branding, therefore this study aims to determine the positive and_x000D_ significant effect partially on price, lifestyle, and Corporate Branding variables_x000D_ on Toyota Agya as LCGC purchasing decisions in Malang City. The research_x000D_ method used is explanatory survey. The research respondents were customers or_x000D_ Toyota Agya as LCGC buyers in Malang, which numbered 130 people, who were_x000D_ selected by the Purposive Sampling method._x000D_ Of the three variables analyzed partially and simultaneously, the price variable_x000D_ coefficient is greater than the other two variables. From the three variables also_x000D_ obtained results that the price variable has a strong influence on purchasing_x000D_ decisions. This means that the price variable has the most influence on the_x000D_ purchase decision of the LCGC in Malang . _x000D_ _x000D_ Keyword : price, life style, Corporate Branding, co branding, buying decission